Predictors of Parenting Stress: The Roles of Family Bonding and Commitment - Ying, Jingjing; Lai, Wang (Journal of Psychosociological Research in Family and Culture, 2023)
Objective: The objective of this study was to explore the relationships between family bonding, family commitment, and parenting stress among parents of children under 18 years old. Method: This cross-sectional study included 220 parents, selected based on the sample size determination table by Morgan and Krejcie (1970). Data were collected using the Parenting Stress Index (PSI), Family Bonding Measure (FBM), and Family Commitment Scale (FCS). Descriptive statistics, Pearson correlation analysis, and linear regression analysis were conducted using IBM SPSS Statistics version 27 to examine the relationships and predictive power of the independent variables on parenting stress. Results: Descriptive statistics showed a mean parenting stress score of 65.35 (SD = 12.47), a mean family bonding score of 78.52 (SD = 10.34), and a mean family commitment score of 81.29 (SD = 9.76). Pearson correlation analysis revealed significant negative correlations between parenting stress and family bonding (r = -0.48, p < 0.001) and between parenting stress and family commitment (r = -0.52, p < 0.001). The regression analysis indicated that family bonding (β = -0.32, p < 0.001) and family commitment (β = -0.40, p < 0.001) significantly predicted parenting stress, accounting for 45% of the variance (R² = 0.45, F(2, 217) = 89.45, p < 0.001). Conclusion: The study findings highlight the significant roles of family bonding and family commitment in reducing parenting stress. Strengthening family bonds and enhancing family commitment can alleviate the stress experienced by parents, leading to better well-being for both parents and children. Interventions aimed at fostering strong family relationships are essential for promoting family resilience and reducing parenting stress.